Implementation of Fuzzy Tsukamoto on Node MCU ESP8266 to optimize monitoring of water flow in pipes - Daru, April Firman; Hirzan, Alauddin Maulana; Duja, Muhammad Alfian Badrud; Christianto, Paminto Agung (International Journal on Perceptive and Cognitive Computing, 2025)
The issue of excessive and uncontrolled artesian water consumption has become a critical concern that requires immediate attention. The lack of real-time monitoring mechanisms often leads to significant water wastage, particularly in urban areas where demand is high. Recent data on artesian water usage indicate a 20% increase in consumption in 2023 compared to the previous year, with approximately 25% of the total distributed water being wasted. To address this issue, an Internet of Things (IoT)-based monitoring system for well water consumption has been developed, integrating the Tsukamoto fuzzy logic method. This system employs a NodeMCU ESP8266 microcontroller to collect water consumption data from a flow sensor. The data is then processed using the Tsukamoto fuzzy logic method to classify water usage into three categories: efficient, normal, and excessive. The categorized water usage information is displayed on a 16x2 LCD and a mobile application, enabling users to monitor their water consumption patterns in real-time.By providing continuous monitoring and intelligent classification of water usage, this system aims to enhance user awareness of sustainable water consumption practices. The results of this study demonstrate that the application of fuzzy logic in the monitoring model enables accurate and adaptive water consumption predictions, which can be adjusted based on environmental conditions. The fuzzy logic values obtained in this study are low flow (0.0), normal flow (0.5), and high flow (0.0). This system is expected to contribute to reducing the risk of excessive water consumption, promoting more efficient resource management, and fostering a culture of conservation among users.